2002
DOI: 10.1152/physrev.00003.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lung Epithelial Fluid Transport and the Resolution of Pulmonary Edema

Abstract: The discovery of mechanisms that regulate salt and water transport by the alveolar and distal airway epithelium of the lung has generated new insights into the regulation of lung fluid balance under both normal and pathological conditions. There is convincing evidence that active sodium and chloride transporters are expressed in the distal lung epithelium and are responsible for the ability of the lung to remove alveolar fluid at the time of birth as well as in the mature lung when pathological conditions lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
649
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 610 publications
(671 citation statements)
references
References 369 publications
10
649
0
4
Order By: Relevance
“…The cause of pulmonary edema in ARDS is unclear. It has been reported that pulmonary edema clearance is greatly affected by active sodium transport out of the alveoli rather than by reversal of the Starling forces (27)(28)(29). In a previous study, we showed that leptospirosis decreases protein expression of the ␣ subunit of the epithelial sodium channel (ENaC) in the lungs of hamsters.…”
Section: Discussionmentioning
confidence: 84%
“…The cause of pulmonary edema in ARDS is unclear. It has been reported that pulmonary edema clearance is greatly affected by active sodium transport out of the alveoli rather than by reversal of the Starling forces (27)(28)(29). In a previous study, we showed that leptospirosis decreases protein expression of the ␣ subunit of the epithelial sodium channel (ENaC) in the lungs of hamsters.…”
Section: Discussionmentioning
confidence: 84%
“…The rate of change in edema fluid protein concentration over time provides an indication of epithelial barrier function as it reflects the clearance of water from the alveolar space over time. Matthay et al 30 document maximal edema clearance rates of [ 14%Áhr -1 with hydrostatic edema. However, the majority of patients with ARDS have reported fluid clearance rates \ 3%Áhr -1 , 1 consistent with the results observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights lack of understanding of the pathways operative in sepsis and the necessity for improved therapies. Impairment of pulmonary vascular integrity is a key feature in multiple pathological conditions, including acute lung injury (ALI), sepsis, lung inflammation, and ventilator-induced lung injury, each of which result in pulmonary edema (1,(5)(6)(7). Sepsis is a complex, serious medical condition consequent to an overwhelming immune response to infection.…”
Section: Introductionmentioning
confidence: 99%